(3JHUQI GdeJYdejf aj CMcGe GdOjfs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3eMeO Hf CHj eMeO GdMGeOi s)
(3ChdgG (B:s
(3GdMeO ddg GdbOje SdWGfg GdYXje TCfg GdhGVM HQgGfg s
(3BNQgG (B:s
(3hjSFd Gddg Cf jLYd Pdc dhLgg NGdUkG Efg bQjH eLjH hHGdELGHI LOjQ hEdjg GdeUjQ hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B222s
Keywords: (3Gdabg GdeGdcjs